2010
DOI: 10.1007/s10826-010-9431-2
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Family Roles Within An Institutional Framework: An Exploratory Study In One Private Chinese Orphanage

Abstract: Current research in child development has espoused the benefit of family-like routines in institutional orphanage care. However, the institutional framework evident in large-group orphanage care often hampers the creation of nurturing, family-like environments. This qualitative study is part of a larger case study exploring how one private Chinese orphanage infuses a family-like structure into an institutional setting. Data is examined from an ecocultural viewpoint, looking at how caregivers and directors' att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…In the present study, the caregivers view themselves as parents to these children as they play a mother or father role to them. The female caregivers in this study are called "mother" which is is in line with findings by Neimetz (2010) where the orphans called their female caregiver "mother" and the male home manager "father". These caregivers' main roles are to provide care and support, but also information for the children.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, the caregivers view themselves as parents to these children as they play a mother or father role to them. The female caregivers in this study are called "mother" which is is in line with findings by Neimetz (2010) where the orphans called their female caregiver "mother" and the male home manager "father". These caregivers' main roles are to provide care and support, but also information for the children.…”
Section: Discussionsupporting
confidence: 88%
“…One important consideration is that, traditionally, institutional settings have been seen as opposed to foster family settings, with the debate focusing on which of them can provide better care for children. A new approach has been looking at how to incorporate family-like roles and routines in residential children's homes (Neimetz, 2011), providing better care for children in need that, for several reasons, do not have access to good quality family care. A large number of children are living in residential children's homes and, if we want to ensure the best outcomes for all children, we need to allow the debate to occur about how best to house children in residential children's homes without losing the perspective that good quality family-based care is the better option, but might not always be available.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…Many of the children came from extended families and environments where they did not receive adequate care due to the strain on the traditional family resources and other domestic issues. Neimetz (2011) indicated that the children's health might lie in how caregivers were able to maintain the dynamics of a traditional family in an institutionalized setting. It is also possible that better health outcomes, particularly mental health, is due to the fact that traditional fostering is a common practice in sub-Saharan Africa, where children are raised by multiple caregivers consisting of kin and non-kin and therefore have the opportunity to live with better-endowed adults (Drah 2012;Hollingsworth 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, the CCIs did produce an "alternative" kinship structure and a family-like environment in which OSCAs could thrive. Neimetz (2011) found that, while not a family in the traditional sense, some institutions established a family-like environment through identification with explicit roles and inclusion of particular daily routines "where children receive [d] the emotional nurturing needed for healthy development" (p. 594). Inadequate family-based care structures as well as inadequate provision of financial support for families taking care of orphans suggest that there is still a place for institutional care in Kenya (Ayuku et al 2014; UNICEF and Republic of Kenya 2013).…”
Section: Discussionmentioning
confidence: 99%